Canine Lymphoma: Retrospective Analysis of the Histopathological Registry of the Istituto Zooprofilattico Sperimentale dell’umbria e delle Marche “Togo Rosati” (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionNeoplasms of the lymphatic system, and in particular lymphoma, represent the most common hematopoietic tumors in dogs and share many similarities with human non-Hodgkin lymphomas (NHLs), both in terms of clinical behavior and cyto-histopathological and immunophenotypic characteristics [1]. Epidemiological data on the incidence of NHLs place them among the top ten cancers by frequency in Italy, equally for men and women, equal to about 3% of all neoplasms. The analysis of incidence trends confirms a substantial stabilization of the increase in new cases in recent dIn veterinary medicine, unfortunately, the acquisition of reliable epidemiological data is difficult, due to the few animal tumor registries present throughout the national territory. The scientific literature on the subject provides fragmentary values showing that lymphoma is, even in the canine species, a very represented neoplastic disease, with incidence rates of 22.9 in females and 19.9 in males [2].AimsThe aims of our observational retrospective study were to analyze the territorial distribution of canine lymphomas in Umbria region and to identify potential risk factors.MethodsA ten-year dataset of canine lymphoma cases examined at the histopathological diagnostic laboratory of the Istituto Zooprofilattico Sperimentale dell'Umbria e delle Marche "Togo Rosati" was evaluated. The study cohort included 4946 dogs, divided into two groups: 202 dogs diagnosed with lymphoma (group K) and 4744 dogs without neoplastic conditions (group NT). Dogs diagnosed with neoplasms other than lymphoma were excluded. Data were collected on individual characteristics including age, sex, breed, body size, geographical location, housing conditions, and dietary habits.  Descriptive analysis was carried out using mean and standard deviation (±sd) or median and interquartile range (IQR) and n (%). Normality distribution for quantitative variables was assessed by the Shapiro-Wilk Test. The association between categorical data was investigated by Pearson χ2 or Fisher's exact test and the Student's t‐test for independent data  or analogue non-parametric test (Wilcoxon rank sum test). Complementary log-log (cloglog) model was applied to identify the mutually adjusted effect among K/NT groups and the independent variables. A statistical significance was set at the level of ≤0.05. All analyses were performed using Stata software v18.0 MP (StataCorp, College Station, USA), GraphPad Prism 10 and geospatial mapping conducted with QGIS 3.40.4.ResultsAmong the 4946 dogs, females were 51.3%, and the mean age was 8.7±3.5 years. A significant lower age was revealed in K group (8.7±3.5 years) vs NT group (9.4±3.3 years), with p=0.004. A statistically association was found between dietary habits and lymphoma group (p